The Effect of Puppet Storytelling to Self Confidence in Elementary School Student - Sari, Desy Purnama; Imron, Hanun Nizar Izdihari; Noviyanti, Rezkika; Pratisti, Wiwien Dinar (Universitas Muhammadiyah Surakarta, 2019)
This study aimed to see whether there is an influence of storytelling puppets on elementary school children’s self-confidence. The method used is Pre-experimental design with pretest-posttest One Group Design. The sampling technique used in this research is purposive sampling informant searches under the criteria set by the researchers, the subject amounted to 304 people is a 5th and 6th-grade students from elementary schools in eight elementary schools scattered in Surakarta. The independent variable in this study is the media storytelling with puppets, while the dependent variable of this study is confidence. Then for the data collection method in this study using observation, the scale of confidence and documentation. Data analysis using SPSS 16 wherein the interpretation of the data obtained using test assumptions, hypothesis testing, and reliability. The results of this study showed no effect of media storytelling with puppets on the confidence of elementary school children. However, when seen from the results of observations made by researchers, data showed that the treatment of storytelling with puppets media can bring behavioral indicators that can be in the observation and these things that can not be served by other studies. The behavior of which is the subject feels up to the task, rarely asking friends but good results, do not care about the taunts, can speak fluently, coherently and systematically, identify strengths and weaknesses.